2020: a wireless video conference in Kenya - Engelhard, Rutger (Technical Centre for Agricultural and Rural Cooperation, 2004)
Rutger Engelhard describes a day in the life of an agricultural extension worker in Kenya and the ICT equipment that he might be using in the year 2020.